Evaluation of maternal qualities of cows of created Simmental Beef breed of different lines - Дедова, Л. О. (Scientific Progress & Innovations, 2013)
The results of the study of maternal qualities of cows of created Simmental beef breed of different lines are given in the article. It has been found that cows of Abrikota, Metz, Ahilesa lines are characterized by the best mothering qualities, reproductive ability. That determines their prospects in the formation of maternal herd. Linear cows of created Simmental beef breeds are characterized by relatively high milk production (1274–1370 kg firstborn, second calving 1345–1535 kg, third and older 1489–1620 kg), which ensures normal growth and development of young animals. Significant differences for milk production between animals of different lines were not found, however cow lines Metz, Ahilesa and Abrikota differed from others with higher milk production. That determines their number in the formation of maternal herd of Simmental beef breed.